An introduction to programming with IDL Interactive Data Language - Bowman, Kenneth P. (Amsterdam ; Boston : Elsevier Academic Press, 2006)
In todays information age, scientists and engineers must quickly and efficiently analyze extremely large sets of data. One of the best tools to accomplish this is Interactive Data Language (IDL®), a programming and visualization environment that facilitates numerical modeling, data analysis, and image processing. IDLs high-level language and powerful graphics capabilities allow users to write more flexible programs much faster than is possible with other programming languages. An Introduction to Programming with IDL enables students new to programming, as well as those with experience in other programming languages, to rapidly harness IDLs capabilities: fast, interactive performance; array syntax; dynamic data typing; and built-in graphics. Each concept is illustrated with sample code, including many complete short programs. Margin notes throughout the text quickly point readers to the relevant sections of IDL manuals End-of-chapter summaries and exercises help reinforce learning Students who purchase the book are eligible for a substantial discount on a student version of the IDL software.
Part I IDL BASICS -- Chapter 1 -- Introduction -- Chapter 2 -- IDL Manuals and Books -- Chapter 3 -- Interactive IDL -- Chapter 4 -- IDL Scripts (Batch Jobs) -- Chapter 5 -- Integer Constants and Variables -- Chapter 6 -- Floating-Point Constants and Variables -- Chapter 7 -- Using Arrays -- Chapter 8 -- Searching and Sorting -- Chapter 9 -- Structures -- PART II INPUT AND OUTPUT -- Chapter 10 -- Printing Text -- Chapter 11 -- Reading Text -- Chapter 12 -- Writing and Reading Binary Files -- Chapter 13 -- Reading NetCDF Files -- Chapter 14 -- Writing NetCDF Files -- PART III PROGRAM STRUCTURE AND CONTROL -- Chapter 15 -- Procedures and Functions -- Chapter 16 -- Program Control -- PART IV GRAPHICS -- Chapter 17 -- Line Graphs -- Chapter 18 -- Contour and Surface Plots -- Chapter 19 -- Mapping -- Chapter 20 -- Printing Graphics -- Chapter 21 -- Color and Image Display -- Chapter 22 -- Animation -- PART V APPLICATIONS -- Chapter 23 -- Statistics and Pseudorandom Numbers -- Chapter 24 -- Interpolation -- Chapter 25 -- Fourier Analysis -- Appendix A An IDL Style Guide -- Appendix B Example Procedures, Functions, Scripts, and Data Files.
Includes bibliographical references (p. 277) and index.
Keywords: Interactive computer systems; Application software -- Development; Mathematical statistics -- Data processing; IDL (programmeertaal); Interactive Data Language (Electronic resource); Electronic books